An overview of laparoscopic versus open incisional hernia repair - Boopathy, D.; Asokan, P. K.; Yeshwanth, T. R. (International Journal of Research in Medical Sciences, 2023)
Background: An incisional hernia is perceived as a morbidity following an abdominal wall operation. Risk factors that increase the chances of developing these hernias are wound infection, male sex, obesity, abdominal distension, underlying disease process and occasionally poor surgical closure. The aim of this study was to compare laparoscopic vs open incisional hernia repair with regard to postoperative pain and nausea, operative time, postoperative complications and length of hospital stay. Methods: We conducted retrospective review of consecutive patients with hernia in department of surgery, Sri Venkateshwaraa Medical College and Hospital, Redhills, Chennai, Tamil Nadu between September 2022 to February 2023 (6 months). We analyzed 140 patients that met the inclusion criteria and their clinical data. The patients were divided into two groups: open incision hernia repair (OI=70) group and laparoscopic hernia repair (LR=70) group. Results: In our study, the mean operative time of 99.64±13.1 min for the laparoscopic repair group was longer than the mean operative time of 74.64±9.14 min for open repair (p =0.264). Hospital stay was not significantly in the laparoscopic group with a mean of 2.4±0.6 days compared with 2.8±1.4 of the open repair group (p=0.0515). Conclusions: Smaller incisional hernias with a transverse diameter <10 cm can be repaired successfully by a laparoscopic approach if a suitably skilled surgeon is available, although an ugly scar may remain on the anterior abdominal wall. Major defects >10 cm was best repaired by an open operation.